Pengaruh Bauran Promosi (Promotion Mix) Terhadap Keputusan Pembelian di Indomaret Telukdalam Kabupaten Nias Selatan - ALUIWAAURI TAFONAO; YURMANIUS WARUWU; ALWINDA MANAO (LPPM Universitas Nias Raya, 2022)
Marketing activities can not be separated in the business world because it has an important function in the survival of a company. Based on the results of observations made by researchers on the object of research, several things about the promotion mix that have not been implemented optimally can be seen from the types of promotions that have been carried out by Indomaret Telukdalam city. Of the many forms of the promotional mix, only a few have been carried out by the company, such as sales promotion programs or discounts, and direct marketing. Several other forms of promotion have not yet been implemented because they are still relatively new in the South Nias district, specifically in Telukdalam city. The purpose of this study was to determine how the influence of the promotion mix on purchasing decisions in Telukdalam City, South Nias Regency. The method used in this study is a type of research with quantitative methods that are associative, namely to determine the relationship between two or more variables. The data collection technique in this study used a questionnaire/questionnaire distribution technique. The results of this study indicate a simple regression of Y = 11.131+0.546X where the constant value (a) of 11.131 is the value of the purchasing decision variable (Y) when the promotion variable is zero and the coefficient value of the promotion variable (b) is 0.546, meaning that each increase in one unit variable promotion will have an impact on increasing the purchasing decision variable by 0.546. The hypothesis test explains that the count for promotion is 10.071 with a significant level of 0.000, while the value is at alpha 0.05 with a degree of freedom (df) n-k-1 (96-1-1) = 94 of 1.661.